Kesadaran Hukum Pengusaha UMKM dalam Pendaftaran Merek Dagang di Kemenkumham Kota Jambi - Abdul Hariss; Nur Fauzia; Puti Indah Ramaya (Wajah Hukum, 2023)
Trademarks as part of the intellectual property rights protected by Indonesia, provided that the mark must be registered in advance with the Ministry of Law and Human Rights of the Republic of Indonesia. Trademark rights serve as a differentiator and identity for a business, one of which is micro, small and medium enterprises (MSMEs), but in reality the legal awareness of MSME entrepreneurs is still relatively low. The formulation of the problem in this study are: 1) What is a trademark and what is its importance for micro, small and medium enterprises (MSMEs)? What causes the low interest of MSME entrepreneurs in registering trademarks at the Jambi City Ministry of Law and Human Rights? 3) How are the efforts being made to increase the legal awareness of MSME entrepreneurs in registering? The research method used is empirical juridical with interview techniques. Based on the research that has been done, it can be concluded that there is a correlation between the low legal awareness of MSME entrepreneurs to register trademarks caused by various factors/causes, the biggest one is the the lack legal awareness of MSME entrepreneurs.